2020
DOI: 10.2981/wlb.00732
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, survival and population growth of killer whales Orcinus orca at subantarctic Marion Island

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 60 publications
(107 reference statements)
1
10
0
Order By: Relevance
“…In Period 1, estimates of apparent survival probability for adult killer whales of both sexes exceeded 0.98 and were higher for females than males throughout the study period (Figure 6a). These results are consistent with estimates from other killer whale populations (Esteban et al, 2016; Fearnbach et al, 2019; Jordaan et al, 2020; Olesiuk et al, 1990, 2005) and with previous analysis of similar data from northern Norway 1986–2003 (Kuningas et al, 2014). A contributing factor to the sex‐specific difference in survival is the extended postreproductive lifespan in females (Foster et al, 2012), which results in a longer mean life expectancy at birth for females than males (46 vs. 31 years in Northern Resident killer whales in British Columbia, Olesiuk et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Period 1, estimates of apparent survival probability for adult killer whales of both sexes exceeded 0.98 and were higher for females than males throughout the study period (Figure 6a). These results are consistent with estimates from other killer whale populations (Esteban et al, 2016; Fearnbach et al, 2019; Jordaan et al, 2020; Olesiuk et al, 1990, 2005) and with previous analysis of similar data from northern Norway 1986–2003 (Kuningas et al, 2014). A contributing factor to the sex‐specific difference in survival is the extended postreproductive lifespan in females (Foster et al, 2012), which results in a longer mean life expectancy at birth for females than males (46 vs. 31 years in Northern Resident killer whales in British Columbia, Olesiuk et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Photo-identification was first applied to killer whales (Orcinus orca) in the north-eastern Pacific in 1973 (Bigg, 1982) and has since led to robust estimates of life-history parameters for a number of discrete populations worldwide (Durban et al, 2010;Esteban et al, 2016;Fearnbach et al, 2019;Jordaan et al, 2020;Kuningas et al, 2014;Olesiuk et al, 1990Olesiuk et al, , 2005Pitman et al, 2018;Tixier et al, 2015Tixier et al, , 2017. As time series of photo-identification data have become increasingly available, they have played a central role in identifying population trends and conservation status.…”
Section: Introductionmentioning
confidence: 99%
“…For long‐lived mammals with delayed maturity and high maternal investment, ecological theory and empirical evidence suggest that adult survival is a stronger driver of population dynamics than juvenile survival or fecundity (Heppell, Caswell, & Crowder, 2000; Runge, Langtimm, & Kendall, 2004). Our results indicated that young calf survival (estimated with temporal variance for the first time here) and breeding adult survival were high and similar to rates reported for other stable cetacean populations (Jordaan et al ., 2020). It is therefore unlikely that increasing breeding female survival is a logistically practical or biologically feasible way to bolster population growth.…”
Section: Discussionmentioning
confidence: 99%
“…Through careful examination of nicks, notches, and scratches on dorsal fins and saddle patches as well as the shape and form of dorsal fins, saddle patches, and eye patches (Bigg et al, 1987), individual killer whales were identified and matched to individuals in identification catalogs (Jordaan et al, 2019; Reisinger & de Bruyn, 2014). A quality score (ranging from 1 to 5 [unusable to excellent]) was assigned to all photographs.…”
Section: Methodsmentioning
confidence: 99%
“…The number of calves born per year ranged from 0 to 4, while the number of reproductive females available for reproduction ranged from 7 to 16 individuals per year (Figure A5), equating to a mean calving rate of 0.11 (95% CI = 0.05-0.17) calves born per year per reproductive female (see also Jordaan et al, 2020). The model assuming constant calving rate over time was most parsimonious (Table 5).…”
Section: Reproduction and Social Structure Analysesmentioning
confidence: 99%